2015
DOI: 10.3329/bjpp.v30i2.22682
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization trends in ENT out patient department in a private teaching hospital in Bangladesh

Abstract: A cross-sectional descriptive study was carried out among individuals attending the ENT out-patient department from 1 st June 2012 to 3Oth August 2012 in Z.H. Sikder Women's Medical College& Hospital, Dhaka. Bangladesh. The primary aim of this study was to generate up to date information on drug use in the ENT outpatient service of our hospital indications for use. A total of 150 prescriptions were randomly audited at varying time interval from the department of ENT during a three month period. The data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
1
1
Order By: Relevance
“…However, various studies reported that P-drug selection exercises should be incorporated into the curriculum. 4 , 6 , 12 , 13 The male-to-female ratio in our study was 1.93 which is higher than that of the previous study with a ratio of 1.45. 4…”
Section: Discussioncontrasting
confidence: 75%
“…However, various studies reported that P-drug selection exercises should be incorporated into the curriculum. 4 , 6 , 12 , 13 The male-to-female ratio in our study was 1.93 which is higher than that of the previous study with a ratio of 1.45. 4…”
Section: Discussioncontrasting
confidence: 75%
“…A study done by Sivakumar P et al (2011) 7 showed that the major ear complaints were CSOM (37.89%), amongst the nasal complaint acute rhinosinusitis was common (56.10%) and amongst the throat complaints tonsillitis was seen in 65.11%. In a similar study conducted by Any OH et al (2014) 10 , amongst the total of 150 patients, maximum cases were of otitis media 74 (49.33%), sinusitis 24 (16.00%), tonsillitis 15 (10.00%), pharyngitis 14 (9.33%), DNS 14 (9.33%), rhinitis 7 (4.66%) and adenoiditis 2 (1.33%).…”
Section: Discussionmentioning
confidence: 82%
“…Bangladesh'te bir hastanede yapılan reçete analizi ile de doktorların tamamının ilaçları ticari isimleri ile yazdıkları, bu nedenle düşük ve orta gelirli aileler için ilaç tutarlarının yüksek olduğu ortaya çıkmıştır. İlaçların jenerik isimleri ile reçetelendirilmesi gerektiği belirtilmiştir [3]. Birleşik Arap Emirlikleri'nde yapılan bir başka çalışmada ise incelenen reçetelerin tamamında jenerik isim tanımlamasının kullanıldığı saptanmış, örneklem üzerinden bir reçetede ortalama 2.6 adet ilaç bulunduğu belirlenmiştir [4].…”
Section: İlişkili çAlışmalarunclassified